Central memory-enriched Vγ9Vδ2 γδ T cells via TGF-β expansion demonstrate enhanced in vivo efficacy against metastatic osteosarcoma - Silva, Jordan A.; Gunasinghe, Kokila; Jonus, Hunter C.; Branella, Gianna M.; Schiaffino Bustamante, Austre Y.; Okalova, Jennifer; Yustein, Jason T.; Spencer, H. Trent (Frontiers in Immunology, 2025)
The application of cellular immunotherapies (CI) for osteosarcoma (OS) has mainly focused on autologous products of αβ T cells and, to date, has shown little clinical benefit. Based on the multi-killing properties of γδ T cells, specifically Vγ9Vδ2 T cells, and their ability to be employed as an allogeneic, off-the-shelf cellular therapy, there is significant interest in this CI. Although there are efficient, clinical-scale expansion protocols, a concern is the short in vivo half-life of these cells due to the terminal differentiated phenotypes of expanded cells. Therefore, modifying the manufacturing process to generate a more memory-like phenotype could overcome hurdles associated with this CI. Transforming growth factor-beta (TGF-β) is a cytokine with multiple functions, and can induce a less differentiated phenotype in γδ T cells. We tested the hypothesis that the in vivo effectiveness of γδ T cells against osteosarcoma (OS) tumors is suboptimal because of the manufacturing process that produces terminally differentiated cells. We combined a modified expansion process with activation strategies known to enhance γδ T cell-based tumor killing. Introducing zoledronate (ZOL) to OS cells augments γδ T cell killing by upregulating phosphoantigens in treated cells, which induces butyrophilin complexes, which are recognized by the TCR of the γδ T cell and significantly increases target cell death in both control and TGF-β expanded γδ T cells. In addition, administering ifosfamide (IFO), a chemotherapy used for relapsed OS, induces stress antigens in OS cell lines that are recognized by NKG2D receptors on γδ T cells, which enhances γδ T cell killing. In vivo studies show the administration of TGF-β expanded γδ T cells, when combined with ZOL and IFO significantly increased overall survival in OS-bearing mice, which we show can be attributed, at least in part, to increased persistence compared to control cells. Together, these data demonstrate this chemoimmunotherapy strategy, which engages various targeting mechanisms of γδ T cells, significantly enhances killing of OS.